PENGARUH KUALITAS SUMBER DAYA MANUSIA, KOMITMEN ORGANISASI, SISTEM PENGENDALIAN INTERN, DAN PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP KUALITAS LAPORAN KEUANGAN (Studi Empiris Pada SKPD Kabupaten Indragiri Hulu) - Maksyur, Noprial Valenra; Tanjung, Amries Rusli; Hariyani, Eka (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to look at the effect of Quality of Human Resources, Organizational Commitment, Internal Control Systems, and Utilization of Information Technology on the Quality of Financial Reports on the regional work units that exist in the District Idragiri Hulu Research carried out on 23 working units that are in Indragiri Hulu 2015. Sampel year that serve as the respondent proposive taken using the sampling method. Each population represented 2 respondents are chief financial sub-section and sub-section staff or the head of financial accounting and accounting field staff. Questionnaires were distributed to 69 respondents, and successfully recovered the complete answer is obtained from 54 respondents. Data were collected from 54 respondents further data were analyzed with SPSS version 17.0 using descriptive statistical analysis and multiple linear regression analysis to produce the classic assumption test, model of data analysis, coefficient of determination and prove the hypothesis. The results partially or simultaneously found that the variable quality of human resources, organizational commitment, internal control systems, and the utilization of information technology affects the quality of financial statementsKeywords: Quality, Commitment, Organizational, Internal Control Systems, and Financial Statements